The Construction of Water-Sensitive Urban Design in the Context of Japan. Issue 1 (March 2021) - Zhang, Yajing; Shen, Zhenjiang; Lin, Yuming
Abstract: Water Sensitive Urban Design (WSUD) is a critical sustainable development theory in the urban water environment, which is attracting more and more attention worldwide. Meanwhile, as an island country, Japan attaches great importance to water resources and water environment, and have achieved fruitful result in urban water management. Based on the framework of WSUD, this research introduces Japan's practical experience from the perspectives of water source protection, flood control, and waterfront space landscape, aiming to summarise Japan's experience and provide a new perspective. By explaining the thoughts of water sensitivity design contained in Japanese practice, this research expands the scope of WSUD, provides a meaningful research framework for Japanese researchers, and provides compelling cases for researchers on water-sensitive design around the world.